Mathematic Communication Ability Reviewed from Linguistic Intelligence in The Collaborative Learning by Using Think-Talk-Write (TTW) Strategy - Setiyawati, Ninik; Junaedi, Iwan; Nugroho, Sunyoto Eko (Journal of Primary Education, 2020)
Mathematical communication ability are competencies that students must owned, but the reality shows that mathematical communication ability are still weak. One strategy that can be done to improve mathematical communication ability is a collaborative model with the TTW strategy. This study has purpose to determine the mathematical communication ability in terms of linguistic intelligence. This study applied a mixed method research with concurrent embedded design and a qualitative research as the primary method. The type of quantitative research used in this study was an experimental research with the Nonrandommized Control Group. The subjects in this study were Grade VII students of MTs Al Miftah Sindangjaya. The data analysis of Learning quality was assessed from the planning, implementation and evaluation stages. Based on data analysis, there were many variations of mathematical communication ability that found as a collaborative work of each group, such as (a) Students with high linguistic intelligence have reached all indicators of mathematical communication ability (b) Students with linguistic intelligence were able to master two indicators of mathematical communication ability well (c) Students with low linguistic intelligence were able to master one indicator of mathematical communication ability well. It can be concluded that TTW can provide good training of linguistic intelligence through collaborative learning. But, the students achievement on mathematical communication were varies tend to dependen their linguistic intelligence.